Reading Contexts, Goals, and Decisions: Text Comprehension as a Situated Activity. Issue 5 (3rd July 2022) - Britt, M. Anne; Durik, Amanda; Rouet, Jean-François
ABSTRACT: The spread of digital technology has prompted an increase in the amount of written text that gets produced and disseminated daily, together with a diversification of reading contexts and purposes. In this article, we propose that modern reading increasingly relies on readers' ability to set up and manage their own reading goals and decisions. We outline our RESOLV theory of purposeful reading and we reflect on students' preparedness for reading in out-of-school contexts. We stress the importance of reading strategies for disciplinary learning but also their limited transfer to out-of-school reading activities. We illustrate this point with an examination of the decisions involved in the reading of fake news. We conclude that students need to be trained to monitor information quality in contexts where neither the reading goal nor the genre and contents of the texts to be read can be expected a priori, which characterizes many current uses of the web.